Arte entre con(tatos): reflexões sobre educação profissional e criação de experiências artísticas relacionais na cidade de Fortaleza - Souza, Gerlane de Albuquerque (2020)
The present work is an investigation on Relational Public Art and the possibilities of contemporary artistic creation in High School (EM). Appropriating the theoretical speeches of Bourriaud (2009) on relational aesthetics, Larrosa's references (2002) on experience and the contributions of Lima (2016) on the design and development of educational materials for the teaching of Visual Arts, the present research has as a general objective to analyze educational experiences on Relational Public Art in professional education, aiming at the expansion of creative processes and pedagogical proposals in the internal and external environments of school institutions. The locus of this study is the teaching teaching unit of the professor-researcher, the State School of Professional Education Maria José Medeiros (EEEP) located in Fortaleza - CE. The interest in the theme arose from the teacher's artistic experiences with the city and from the need to expand, as an educator, contemporary artistic practices that explore urban spaces. Relational Art, as an excerpt from Contemporary Art, has presented itself as a fertile field for ephemeral, hybrid and interrelational artistic experiments that provide new ways of reinventing everyday life and the relationship between man and the world. However, introduced in the educational field, what would be the possible contributions that this theme would bring to the teaching of Art in professional schools? Seeking to obtain answers to this problem, this study appropriated a research in Art teaching with a qualitative approach based on the ethnographic method. To operationalize the research, a group of 39 2nd year students of the technical nursing course was part of the study, with data being produced through the teacher's field diaries, semi-structured interviews, preparation of the lesson plan, experience reports and photographic records students' creative process. From the processes experienced in this research, on the results, it was found that students expanded the ways of thinking and making art; it was also noted that artistic making in urban environments contributed to the construction of knowledge in relational art, expanding the limits of learning places, as well as cooperating, through the creation of a pedagogical proposal, for the expansion of creative and aesthetic strategies that contribute to the insertion of art in daily life.